Data and Applications Security XX 20th Annual IFIP WG 11.3 Working Conference on Data and Applications Security, Sophia Antipolis, France, July 31-August 2, 2006, Proceedings - Damiani, Ernesto; Liu, Peng (Information Systems and Applications, incl. Internet/Web, and HCI, 2006)
For 20 years, the IFIP WG 11. 3 Working Conference on Data and Appli- tions Security (DBSEC) has been a major forum for presenting originalresearch results, practical experiences, and innovative ideas in data and applications - curity. Looking back, it is di?cult not to appreciatethe full extent of the change that has occurred in our ?eld. Once considered afterthoughts in systems and application design, data protection, privacy and trust have become the key problems of our day. This central role of security in the information society has however brought increased responsibilities to the research community. - day practitioners and researchers alike need to ?nd new ways to cope with the increasing scale and complexity of the security problems that must be solved on the global information infrastructure. Like the previous conference, the 20th DBSEC has proved to be up to this challenge. DBSEC 2006 received 56 submissions, out of which the program committee selected22 high-qualitypaperscoveringanumber of diverseresearchtopicssuch as access control, privacy, and identity management. We are glad to see that the ?nal program contains a well-balanced mix of theoretical results and practical prototype systems, many of them converging and building o? each other. Also, the DBSEC program includes a number of papers on new, emerging aspects of security research. Putting together a top-level conference like DBSEC is always a team e?ort.